The Add-On Effect of Lactobacillus plantarum PS128 in Patients With Parkinson's Disease: A Pilot Study - Lu, Chin-Song; Chang, Hsiu-Chen; Weng, Yi-Hsin; Chen, Chiung-Chu; Kuo, Yi-Shan; Tsai, Ying-Chieh (Frontiers in Nutrition, 2021)
Background: Lactobacillus plantarum PS128 (PS128) is a specific probiotic, known as psychobiotic, which has been demonstrated to alleviate motor deficits and inhibit neurodegenerative processes in Parkinson’s disease (PD)-model mice. We hypothesize that it may be also beneficial to patients with PD based on the possible mechanism of interrupting transportation of neurotoxins via the microbiome-gut-brain axis. Methods: This is an open-label, single-arm, baseline-controlled trial. The eligible participants were scheduled to take 60 billion colony-forming units of PS128 once per night for 12 weeks. Clinical assessments were conducted using the unified Parkinson’s disease rating scale (UPDRS), modified Hoehn and Yahr stage, and change in patient "ON-OFF" diary recording as primary outcome measures. The non-motor symptoms questionnaire, Beck depression inventory 2nd edition, patient assessment of constipation symptom, 39-item Parkinson’s disease questionnaire (PDQ-39), and patient global impression of change (PGI-C) were assessed as secondary outcome measures. Results: Twenty-five eligible patients (32% women) completed the study. The mean age was 61.84 ± 5.74 years (range, 52-72), mean disease duration was 10.12 ± 2.3 years (range, 5-14), and levodopa equivalent daily dosage was 1063.4 ± 209.5 mg/daily (range, 675-1560). All patients remained on the same dosage of anti-parkinsonian and other drugs throughout the study. After 12 weeks of PS128 supplementation, the UPDRS motor scores improved significantly in both the OFF and ON states (p=0.004 and p=0.007, respectively). In addition, PS128 intervention significantly improved the duration of the ON period and OFF period as well as PDQ-39 values. However, no obvious effect of PS128 on nonmotor symptoms of patients with PD was observed. Notably, the PGI-C scores improved in 17 patients (68%). PS128 intervention was also found to significantly reduce plasma myeloperoxidase and urine creatinine levels. Conclusion: Therefore, the present study demonstrated that PS128 supplementation for 12 weeks with constant anti-parkinsonian medication improved the UPDRS motor score and quality of life of PD patients. We suggest that PS128 could serve as a therapeutic adjuvant for the treatment of PD. In the future, placebo-controlled studies are needed to further support the efficacy of PS128 supplementation. Clinical Trial Registration: https://clinicaltrials.gov/, identifier: NCT04389762